Поетика іменності та безіменності у художньому тексті (Частина І. Ім’я vs тимчасова безіменність) - Загнітко, Анатолій; Кравченко, Елла (Slavia Orientalis, 2025)
The article is devoted to the problem of interaction between nameness and namelessness within artistic text. Various means of designating the objects of artistic space that are named or remain nameless are identified. The phenomenon of the temporal namelessness (the absence of a proper name for an artistic object at a certain stage of text unfolding) is analysed. The author proves the significant role of temporary (complete / incomplete / false) namelessness for the interpretation of the imagery of the poetonym, plot dynamics and the poetics of text. The movement from nameness to namelessness leads to the transformation (transformation, regression, degradation, change of appearance or essence, etc.) of the artistic image. It is proved that the complete / partial loss of the name marks the stage of the poetonym evolution and makes it possible to transform the proper name into a connotonym or a symbol. The interpretation of the complicity of temporal nameness – namelessness in textual formation with the definition of the reasons and motivations for the name denial always works for the interpretation of the integrity.